A New Approach to Identification of Critical Elements in Railway Infrastructure. (2017) - Leitner, Bohus; Môcová, Lenka; Hromada, Martin
Abstract: The paper contains a presentation of new approaches to solving the problem of identifying critical infrastructure elements in the railway sub-sector. The research objective was to analyse the procedures which are used to identify the potential elements of critical infrastructure in the transportation sector. Specific attention is paid to criteria of methods developed in Germany, the Czech Republic and Slovakia. The objective of the work is based on the analysis of the current state of art. The research also attempted to design an effective methodology which allows assessing the significance of rail infrastructure elements. The developed methodology should help to set a group of potential elements of critical infrastructure in the railway sub-sector.